Implementation of the Critical Path Method (CPM) in the Flower House Construction Project - Galang Pramuja; Dimas Aditya; Ahmad Ridwan; Anggi BR Pasaribu; Rahmat Hidayat; Lamhot Pasaribuf; Vidi Agung Fragastia (LPPM Universitas Potensi Utama, 2025)
The project management approach plays an important role in controlling project activities carried out to minimize time and cost risks. Project management is usually used in construction projects such as general development to research and development activities. One crucial aspect in project management is scheduling the implementation time. Scheduling serves to determine the sequence, duration, and relationship between project activities. This research writing uses a quantitative research design by collecting primary and secondary data relevant to the research questions. This research also uses the Critical Path Method (CPM) approach, which is a method used to analyze project scheduling and project time planning as well as find critical paths to determine effective and optimal time in completing a project. This research was conducted on the Flower House Construction project at PT. XYZ. The results of this study indicate that the critical path obtained is as many as 6 activities or jobs, namely, (A) Measurement and installation of bowplanks, (B) Making and assembling iron poles, (D) Installation of iron poles, (E) Installation of stones for walls, (F) Plastering walls, (H) Painting and finishing. The critical path obtained from start to finish is 1 – 2 – 3 – 5 – 6 – 7 – 9.